Politics in the blood the Anthonys of Richmond - Davey, Paul (University of New South Wales Press, 2008)
"Biography of three generations of the one family (Hubert, Doug and Larry Anthony), all of whom for over some 70 years held the Federal seat of Richmond in NSW for the National Party. Note that the hold on the seat was not continuous for this entire period. Author is also a member of the National Party)".--Provided by publisher.